Creation of Provision for Doubtful Debts - Sigidov, Yuriy Ivanovich; Korovina, Marina Aleksandrovna; Trubilin, Aleksander Ivanovich; Govdya, Viktor Vilenovich; Vasilieva, Nadezhda Konstantinovna (International Journal of Economics and Financial Issues, 2016)
The purpose of this study is to develop methods of creation of provision for doubtful debts. It was proposed to use two methods of provisioning for doubtful debts, both individually and in the aggregate. The first method is percentage of sales approach that is used in international standards. Its use requires to calculate the average percentage of doubtful debt by determining the average ratio of the outstanding accounts receivable to revenue volume over 3-5 years. This method is recommended for use to organizations with a large number of debtors with minor amounts of debts. The second method, developed by the authors, takes into account the timing of incurring of debt, the solvency of the debtor and the risk of non-repayment. It is advisable to apply for debtors with significant amounts of debt. Using the author's method, the provision for doubtful debts was calculated according to the data from the existing company "Elephant" LLC for 2015, which resulted in revealing the deviation in the amount of the provision from the actual data. The use of the proposed methods will improve the reliability of the accounting (financial) statements in terms of the reflection of the receivables and simplify the work of accountants in finding a method to create a provision for doubtful debts. Keywords: receivables, doubtful debt, provision, creation, method JEL Classifications: M40, M41, M49